Influences of intraperitoneally and dietary administered vitamin E and selenium on the lipid composition in reproductive organs of male animals - Yilmaz, O; Celik, S; Dilsiz, N (Walter de Gruyter & Co, 1997)
The aim of this work was to determine the protective effect of intraperitoneally and dietary administered vitamin E and selenium (Se) on the total lipid, cholesterol, and fatty acid composition in rat and lamb testes. The level of total lipid in rat testes was significantly decreased (p < 0.001) in the combination group as compared to the control group but slightly decreased in lamb testes (p < 0.05). In addition, the level of total lipid in lamb testes was significantly decreased (p < 0.001) by the Se alone. The content of total cholesterol in rats was higher in the Se group and its level in lamb testes was higher in the vitamin E groups than in the control group (p < 0.001). In rats testes, the amounts of palmitic, oleic, arachidonic acids, the total fatty acid, total unsaturated and total omega 6 acids were higher (p < 0.001) in the Se group, The proportions of palmitic and arachidonic acids were reduced in the vitamin E group and linoleic acid, total unsaturated, and total omega 6 fatty acids were high (p < 0.05) in the vitamin E and combination groups. In lamb testis tissues, the amounts of palmitic, arachidonic, total unsaturated and total cr, 6 fatty acids were decreased in the vitamin E group in comparison to the control (p < 0.05). However, the amounts of arachidonic and total omega 6 fatty acids Increased (p < 0.05) in the Se group. The proportions of arachidonic acid, total unsaturated fatty acid and total omega 6 fatty acids were high (p < 0.05) in the Se and combination groups. We concluded that the level of total lipid in testis tissues was reduced by dietary and intraperitoneally administered vitamin E and Se together. In contrast, it seems that the proportions of unsaturated and essential fatty acids in examined tissues are increased by vitamin E and Se.
Keywords: cholesterol; fatty acids; selenium; testis tissues; total lipid; vitamin E